FAKTOR-FAKTOR YANG MEMPENGARUHI KOLEKTIBILITAS KREDIT DI BANK X CABANG Y - , Ratih Damayanti, S.E, Dr. BM. Purwanto, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
As long as the bank gives credit, then, having problems with credit is a common thing because the essence risk of giving credit is default risk. However, the bank has always to make efforts to suppress the credit problem, in order that, in the end, it wonât affect the bankâs activities. This research is aimed to analyze factors that influence the credit collectivities in Bank X subdivision Y, which can reveal how big is the capabilities of a client whoâs in debt (debitor) to return the credit he received to the bank that gives credit (creditor) which suitable prior to the agreement. Therefore, if those factors are revealed, then, later, we can minimize the emergence of credit problem in the Bank X subdivision Y. This research uses descriptive qualitative method, which constitutes an attempt to describe what kind of factors that influence the credit collectivities in Bank X subdivision Y. Primary data are collected by using unstructured interview with the related correspondents to the credit given by Bank X subdivision Y. Then, secondary data are collected through financial and non-financial reports of the Bank itself. According to the interview as well as secondary data, this research concludes that factors that influence the collectivity credit come from two parties, which are the bank and the debitor. Creditor factors are guarantee, memo of understanding (MOU), technical ability of credit analysis, Debitor Information System, bankâs understanding of debitorâs financial, and monitoring. Debitor factors are improper intention and lack of intention to cooperate